2017
DOI: 10.2147/idr.s148185
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of colistin mono- and combination therapy against colistin-resistant <em>Acinetobacter baumannii,</em> mechanism of resistance, and clinical outcomes of patients infected with colistin-resistant <em>A. baumannii</em> at a Thai university hospital

Abstract: PurposeColistin is a drug of last resort for treating multidrug-resistant Acinetobacter baumannii infections. Unfortunately, colistin-resistant A. baumannii (CoR-AB) has been reported. Here, we examined the in vitro effect of mono- and combined antimicrobials against CoR-AB strains and their resistance mechanism, and evaluated the clinical outcomes of CoR-AB-infected patients.Patients and methodsSeventeen clinical CoR-AB strains were isolated from patients at Phramongkutklao hospital, 2011–2015. The mono- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 17 publications
3
26
0
Order By: Relevance
“…Due to the limitation of treatment of carbapenem-resistant A. baumannii infection, colistin is becoming frequently used as a last alternative. No colistin-resistant A. baumannii was found in our study and colistin-resistant strains have rarely been recovered among carbapenem-resistant A. baumannii isolated from Thailand [26]. Nevertheless, the emergence of this critical pathogen, carbapenem-resistant A. baumannii requires new active agents for treatment.…”
Section: Plos Onementioning
confidence: 51%
“…Due to the limitation of treatment of carbapenem-resistant A. baumannii infection, colistin is becoming frequently used as a last alternative. No colistin-resistant A. baumannii was found in our study and colistin-resistant strains have rarely been recovered among carbapenem-resistant A. baumannii isolated from Thailand [26]. Nevertheless, the emergence of this critical pathogen, carbapenem-resistant A. baumannii requires new active agents for treatment.…”
Section: Plos Onementioning
confidence: 51%
“…A critical problem is the increasing prevalence of carbapenem resistance, particularly by the mechanism of carbapenemase production (Codjoe and Donkor 2017). In this study, most of the CRAB isolates harbored one or two OXA carbapenemase genes, bla OXA-23-like and/ or bla OXA-58-like , similar to previous studies from Thailand (Lertsrisatit et al 2017;Leungtongkam et al 2018). In agreement with other reports, bla OXA-23-like was the major resistance determinant (40-100%) among the CRAB isolates, indicating that carbapenem monotherapy is now no longer used as a therapeutic option against the MDR A. baumannii infections (Ezadi et al 2019;Salehi et al 2018).…”
Section: Discussionsupporting
confidence: 86%
“…Lertsrisatit et al has shown that colistin monotherapy is not optimal for treatment of CoRB. In this paper, all (17 of 17) CoR-AB isolates were susceptible to tigecycline and were partially susceptible to sulbactam, imipenem, meropenem, and cotrimoxazole in vitro [91]. A retrospective cohort study revealed gentamicin markedly reduced mortality caused by CoR-AB triggered sepsis, especially in urinary tract infections [63].…”
Section: Treatment For Corb Infectionsmentioning
confidence: 99%